1993
DOI: 10.1093/oxfordjournals.annonc.a058484
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic pathology of ovarian cancer from the Vaud Cancer Registry, Switzerland

Abstract: The present report is a population-based description of the epidemiologic pathology and prognosis of ovarian cancer, and provides evidence of a significant improvement of survival over the past decade. This may be due to changed diagnostic methods (e.g., ultrasonography), improved surgical approach, (platinum-based) chemotherapy, or a combination of all these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
27
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 15 publications
9
27
2
Order By: Relevance
“…The age-specific incidence rates by histology subtype observed in this study showed patterns similar to those reported in previous studies based on data from the US Third National Cancer Survey (Weiss et al, 1977), the Danish Cancer Registry (Ewertz et al, 1988) and the Vaud Cancer Registry in Switzerland (Levi et al, 1993).…”
Section: Discussionsupporting
confidence: 89%
“…The age-specific incidence rates by histology subtype observed in this study showed patterns similar to those reported in previous studies based on data from the US Third National Cancer Survey (Weiss et al, 1977), the Danish Cancer Registry (Ewertz et al, 1988) and the Vaud Cancer Registry in Switzerland (Levi et al, 1993).…”
Section: Discussionsupporting
confidence: 89%
“…This finding is similar to the findings of Shy et al 24 and Di et al 13 In this study serous cystadenocarcinoma constituted the most common malignant tumor (26.6%) as shown by various other studies. 19,20,26 Age Age range of 10 -86 years was seen in this study with the mean age of 39.1. Similar results were reported by Ahmed et al 22 and Chow et al 12 19 in his study has shown a case of benign cystic teratoma in 7months child.…”
Section: 17%) Whereas DImentioning
confidence: 53%
“…Since 1976, a registration scheme, applying the same standardized rule as for incident malignancies, has been implemented for borderline ovarian tumours (Levi et al, 1993). Bilateral ovarian tumours (either synchronous or metachronous) are not registered separately, unless histologically different.…”
Section: Methodsmentioning
confidence: 99%